The Analysis of Female Masculinity as a Form of Uprising in Song Lyric by Musician Ramengvrl - Maria Sisilia Sinta Saputra; Riris Mutiara Paulina Simamora (e-LinguaTera, 2022)
Ramengvrl is one of the female musicians in the world of hip-hop, in this thesis the writer chooses five songs. Those are â€œIm Da Manâ€, â€œDecideâ€, â€œI AM MEâ€, â€œLook At Me Nowâ€, â€œDonâ€™t Touch Meâ€. In order to analyze it, this research was conducted by using Female Masculinity and also Liberal Feminism theory. This research used qualitative methodology to analyze the song lyrics. This research sees how Ramengvrl wrote her lyrics as a media to express what she feels and thinks. Moreover, this research aims to find the concept of Female Masculinity depicted in song lyrics by Ramengvrl since she is working in the hip-hop industry where male domination is still quite strong. The research findings can be cited in the research literature in educational institutions and other places. It is also considered to be useful in a variety of ways.